En la hora de la barbarie: múltiples marxismos e identidad de izquierda en Bolívar Echeverría - González Jiménez, Fernando Alejandro (2022)
This essay makes a interpretation of Bolívar Echeverría’s text entitled “In the hour of barbarism” from 1983, which embodies the very first version of the presentation of the 1985 book The Critical Discourse of Marx. In this primal version, the author offers his balance of the 20th century, written during its final decades, and also puts the basis to rebuild his idea of “multiple marxisms” and the so called “Marx substance”, as well as his critical consideration of the identity of the comunist left.